Calculation of the Influence Zone for Planetary Sampling Based on DEM Simulation - Qian Li; Junping Li; Lanlan Xie (International Journal of Aerospace Engineering)
In the design of planetary sampling devices, calculating the reaction force acting on the sampling devices is crucial. According to related research, the influence zone caused by sampling plays an important role in calculating the reaction force. A new method for estimating the range of the influence zone based on 3D DEM simulation is discussed in this paper. Taking lunar soil as an example, first, via validation of physical experiments, the DEM lunar soil simulant was proven to have mechanical properties similar to those of real lunar soil. Second, stress was selected as an indicator to identify the influence zone by computing the match percentage via a comparison between classical soil mechanics and DEM simulation. Using the proposed calculation method, it can be observed that the trend of change of influence zone at different sampling moments showed similar to the change of reaction force. Calculation of the influence zone can be used to analyze the reaction force of different gravity environments, sampling device structures, and motions.